(untitled) - Omura, George (Indianapolis, 2006)
If you're new to AutoCAD, the tutorials will help you build your skills right away. If you're an AutoCAD veteran, Omura's in-depth explanations of the latest and most advanced features, including all the new 3D tools, will turn you into an AutoCAD pro. Whatever your experience level and however you use AutoCAD, you'll refer to this indispensable reference again and again.
Keywords: AutoCAD,Computer graphics,Đồ họa máy tính,Autocad